Comparison of soil frost depth and its duration determined by soil frost tube and soil temperature interpolation - STŘEDOVÁ, Hana; FUKALOVÁ, Petra; STŘEDA, Tomáš (Contributions to Geophysics and Geodesy, 2012)
Soil frost and the depth of freezing are important for the plant development and for the building industry as well. The depth of soil frost is estimated directly by soil frost tube and indirectly from diagrams of soil temperature according to the isotherm of 0 °C (zero-isotherm). The soil temperature measurement is often used for evaluation of freezing depth, because the frost tubes measurement is rarely performed. Measurement by frost tube is done once a day at 7 a.m. and soil temperature in 5, 10, 20, 50 and 100 cm is measured in three observation terms at 7 a.m., 2 p.m. and 9 p.m. Data from agroclimatological station Pohořelice (1971–2000) were used for the evaluation. Three specific real cold periods (1978–1979, 1984–1985 and 1990–1991) and mean frost depth and absolute maximal frost depth for the whole period were evaluated. Course of frost, terms of beginning and the end of frost period and the term of maximum freezing assessed by both methods are almost identical in all real evaluated periods. The results show that the soil frost depth measured by soil frost tube is often higher than that estimated from soil temperature diagrams. It might be caused by graphical processing, as soil temperatures are measured only at five given depths and the depth of zero isotherm is determined by their interpolation. The most significant differences between both methods were observed when evaluating average values for the entire period 1971–2000.